Race and Insurance Disparities in Discharge to Rehabilitation for Patients with Traumatic Brain Injury - Asemota, Anthony O. (Mary Ann Liebert, Inc., 2013)
Post-acute inpatient rehabilitation services are associated with improved functional outcomes among persons with traumatic brain injury (TBI). We sought to investigate racial and insurance-based disparities in access to rehabilitation. Data from the Nationwide Inpatient Sample from 2005–2010 were analyzed using standard descriptive methods and multivariable logistic regression to assess race- and insurance-based differences in access to inpatient rehabilitation after TBI, controlling for patient- and hospital-level variables. Patients with moderate to severe TBI aged 18–64 years with complete data on race and insurance status discharged alive from inpatient care were eligible for study. Among 307,675 TBI survivors meeting study criteria and potentially eligible for discharge to rehabilitation, 66% were white, 12% black, 15% Hispanic, 2% Asian, and 5% other ethnic minorities. Most whites (70%), Asians (70%), blacks (59%), and many Hispanics (49%) had insurance. Compared with insured whites, insured blacks had reduced odds of discharge to rehabilitation (odds ratio [OR] 0.84; 95% confidence interval [CI] 0.75–0.95). Also, insured Hispanics (OR 0.52; 95% CI 0.44–0.60) and insured Asians (OR 0.54; 95% CI 0.39–0.73) were less likely to be discharged to rehabilitation than insured whites. Compared with insured whites, uninsured whites (OR 0.57; 95% CI 0.51–0.63), uninsured blacks (OR 0.33; 95% CI 0.26–0.42), uninsured Hispanics (OR 0.27; 95% CI 0.22–0.33), and uninsured Asians (OR 0.40; 95% CI 0.22–0.73) were less likely to be discharged to rehabilitation. Race and insurance are strong predictors of discharge to rehabilitation among adult TBI survivors in the United States. Efforts are needed to understand and eliminate disparities in access to rehabilitation after TBI.